MICROTREMOR ANALYSIS IN DETERMINING LANDSLIDE POTENTIAL IN SEMBAHE VILLAGE, SIBOLANGIT DISTRICT, DELI SERDANG REGENCY - Lubis, Rahmadhani; Sirait, Ratni; Lubis, Lailatul Husna (EINSTEIN (e-Journal), 2024)
Sembahe Village is an area that is highly vulnerable to landslides. This is caused by steep topographic conditions and high rainfall. This research is intended to understand the characteristics and distribution of dominant frequencies, amplification factors and seismic vulnerability index on the possibility of landslides. Microtremor measurements were carried out in Hamlet 3 Sembahe Village at 2 location points which were measured using a portable seismograph / Pegasus for 2 hours with a sampling frequency. 100 Hz. Microtremor data was processed using Geopsy software using the Horizontal to Vertical Spectral Ratio (HVSR) method and each parameter was weighted using the Analytical Hierarchy Process (AHP) statistical method in determining potential landslide areas. The results obtained show that the distribution of dominant frequency values (F0) is 5.36 Hz – 5.33 Hz, amplification (A0) is 1.84 – 1.59, seismic vulnerability index (Kg) is 0.63 x 10-3s2 / cm - 0.47 x 10-3 s2/cm. Based on weight analysis using the AHP statistical method, the location point that has the highest potential for landslides is point 1